Evaluasi Kinerja Petugas Distribusi Berkas Rekam Medis Rawat Jalan di RSUD dr. Saiful Anwar Malang - Najla Kamil; Dony Setiawan Hendyca Putra; Feby Erawantini; Niyalatul Muna (Politeknik Negeri Jember, 2020)
Patrang Health Center has implemented medical records management, but there are problems in the implementation of medical record management. when duplicating medical record numbers at Patrang Health Center. Duplication in the Patrang Community Health Center results in a decrease in the quality of medical records. The purpose of this study was to analyze the causal factors and determine the priority causes of duplicate medical record numbers at Patrang Health Center. This type of research is qualitative. The technique of collecting data in this study is observation of data duplication of medical records and interviews with respondents based on 7M indicators. Data processing with CARL criteria. The results of this study were found in studies that found the main priority of less useful duplication of the medical record number on the medical record data map with a score of 144. Further problems were officers, filing space was less extensive, filing shelves were inadequate and patients did not carry KIB with a score 108. With the discovery of priorities leading to duplication, the study provides the main solution that discusses the medical record number written on the front and sides of the file as well as other solutions to overcome the problem and made a draft policy to reduce the incidence of duplicate medical record numbers that have been approved.